Sectional Circular Gradient Grating with Improved Focusing Characteristics in THz Frequency Range - Dzubenko, M. I.; Radionov, V. P.; Maslov, V. A.; Odarenko, E. N. (IEEE, 2020)
A method for increasing the focusing properties of annular gradient gratings is presented in this work. The interaction of the coherent radiation of the terahertz range with gradient gratings consisting of concentric metal rings is investigated. The thickness and width of the metal rings is much less than the radiation wavelength. The distance between the rings varies in the radial direction, but does not exceed half the wavelength. It was previously found that such planar structures have focusing properties. Moreover, they can simultaneously serve as a concave mirror and a focusing lens. The combination of these properties is promising for laser output mirrors. This makes it possible to reduce diffraction losses in the laser cavity and improve the spatial and angular characteristics of the laser beam. In addition, laser radiation acquires azimuthal polarization, which has certain advantages. In some cases, an increase in the focusing properties of gradient gratings is required. A significant increase in focusing properties can be achieved by sectioning according to the principle of Fresnel lenses. However, phase inhomogeneities arise at the boundaries of the sections. This disrupts focus and introduces additional loss. In the work, a method for increasing the focusing properties of sectioned circular gradient gratings by giving them a stepped shape is considered. The results of modeling such gratings are presented.
Keywords: gradient circular grating; phase step; terahertz range; focusing properties